2000
DOI: 10.1034/j.1600-0412.2000.079002113.x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of stress and state anxiety on the outcome of IVF‐treatment: Psychological and endocrinological assessment of Swedish women entering IVF‐treatment

Abstract: The main findings suggest that infertile women have a different personality profile in terms of more suspicion, guilt and hostility as compared to the fertile controls, perhaps as a response to their infertility. Their stress levels in terms of circulating prolactin and cortisol levels were elevated compared to the fertile controls. Psychological stress may affect the outcome of IVF treatment since state anxiety levels among those who did not achieve pregnancy were slightly higher than among those who became p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
150
4
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(164 citation statements)
references
References 11 publications
4
150
4
4
Order By: Relevance
“…21,35 Not surprisingly, infertility is associated with increased levels of stress, anxiety and depression, 10,23 suggesting that any effects attributed to estradiol changes in fact may be related to reduced coping/cooperation or increased sensitivity due to the different biological effects of long-term stress. Still, Verhaak et al, 44 reviewing 25 years 13 of research on emotional reactions in women undergoing IVF treatment, found that subjects in the treatment phase, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…21,35 Not surprisingly, infertility is associated with increased levels of stress, anxiety and depression, 10,23 suggesting that any effects attributed to estradiol changes in fact may be related to reduced coping/cooperation or increased sensitivity due to the different biological effects of long-term stress. Still, Verhaak et al, 44 reviewing 25 years 13 of research on emotional reactions in women undergoing IVF treatment, found that subjects in the treatment phase, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…High levels of psychological stress, anxiety, insomnia, depression, and sexual function changes have been reported during in vitro fertilization-embryo transfer (IVF-ET) [1][2][3][4][5][6]. These are related to a number of stresses that are the results of both the diagnosis and treatment of infertility [7].…”
mentioning
confidence: 99%
“…Many women consider infertility to be the most stressful experience in their lives [3], and stress may affect IVF outcomes [3][4][5][6]. In our experience, patients feel that they may experience less stress if their own physician performs the embryo transfer, and wonder if pregnancy would be more likely to occur.…”
Section: Discussionmentioning
confidence: 84%